Оценка виброактивности компрессорной установки передвижной компрессорной станции - Гапонов, Владимир Степанович; Мац, В. И.; Наумов, Александр Иванович (НТУ "ХПИ", 2009)
The question of estimation of vibroactivity of turning vibrations is examined in the system engine-compressor of low pressure in the options of the movable compressor stations. It is revable that for such sort of the systems, possessing muffs with toroid-shape shell, possessing high pliability, the task is taken to the decision of the dynamic systems with multifrequency excitation.
Keywords: приводы станций; крутильные колебания; торообразная оболочка; двухмассовая система